Health Evaluation of Fenghe River Based on AHP-Fuzzy Mathematical Model and Item-by-Item Evaluation Method - ZHANG Zeyang; LIU Qiang; WANG Gang; XU Ziwei (Renmin Zhujiang)
This paper takes Fenghe River in Langfang City as the research object to conduct river health evaluation,which is expected to provide a direction for the future health management of Fenghe River and achieve the goal of healthy development of the water ecology of local rivers.On the basis of the relatively perfect evaluation standard,the scientific and reasonable health evaluation of Fenghe River is carried out by the item-by-item evaluation method and the AHP-fuzzy mathematical model,which is suitable for the local actual situation.An evaluation system is constructed,which consists of four criterion layers covering “basin”,“water”,“biology”,and social service functions and 12 subordinate index layers.The evaluation results show that Fenghe River is healthy according to the item-by-item evaluation method.In the evaluation of the AHP-fuzzy mathematical model,Fenghe River is “very healthy”,with a grade of 0.411 0.By this method,the grade of “healthy” is 0.343 8,and the grades of 0.223 9,0.021 3,and 0 denote the health status of “sub-healthy”,“unhealthy”,and “bad”,respectively.The Fenghe River Basin in Langfang Economic and Technological Development Zone has poor performance in terms of riparian bandwidth,sediment pollutants,and water quality.The proposed evaluation method can provide a reference for the health evaluation of rivers heavily influenced by cities and artificial interventions.